To find the product of the polynomials \((x^2y + 2)(x^2 - y)\), we can use the distributive property (also known as the FOIL method for binomials).
Let's expand the expression:
\[ (x^2y + 2)(x^2 - y) \]
-
Distribute \(x^2y\):
- \(x^2y \cdot x^2 = x^4y\)
- \(x^2y \cdot (-y) = -x^2y^2\)
-
Distribute \(2\):
- \(2 \cdot x^2 = 2x^2\)
- \(2 \cdot (-y) = -2y\)
Now, combine all the terms:
\[ x^4y - x^2y^2 + 2x^2 - 2y \]
So the product of the polynomials is:
\[ \boxed{x^4y - x^2y^2 + 2x^2 - 2y} \]
The correct response from your options is:
x^4y - x^2y^2 + 2x^2 - 2y